Variation potential influence on photosynthetic cyclic electron flow in pea - Sukhov, Vladimir; Surova, Lyubov; Sherstneva, Oksana; Katicheva, Lyubov; Vodeneev, Vladimir (Frontiers in Plant Science, 2015)
Cyclic electron flow is an important component of the total photosynthetic electron flow and participates in adaptation to the action of stressors. Local leaf stimulation induces electrical signals, including variation potential (VP), which inactivate photosynthesis; however, their influence on cyclic electron flow has not been investigated. The aim of this study was to investigate VP’s influence on cyclic electron flow in pea (Pisum sativum L.). VP was induced in pea seedling leaves by local heating and measured in an adjacent, undamaged leaf by extracellular electrodes. CO2 assimilation was measured using a portable gas exchange measuring system. Photosystem I and II parameters were investigated using a measuring system for simultaneous assessment of P700 oxidation and chlorophyll fluorescence. Heating-induced VP reduced CO2 assimilation and electron flow through photosystem II. In response, cyclic electron flow rapidly decreased and subsequently slowly increased. Slow increases in cyclic flow were caused by decreased electron flow through photosystem II, which was mainly connected with VP-induced photosynthetic dark stage inactivation. However, direct influence by VP on photosystem I also participated in activation of cyclic electron flow. Thus, VP, induced by local leaf-heating, activated cyclic electron flow in undamaged leaves. This response was similar to photosynthetic changes observed under the action of direct stressors. Possible mechanisms of VP’s influence on cyclic flow were discussed.